FAKTOR-FAKTOR MENURUNNYA JUMLAH PEMBIAYAAN PADA BPRS AL-WASHLIYAH MEDAN - Cindy Triningsih; Ahmad Amin Dalimunte (Al-Qashdu : Jurnal Ekonomi dan Keuangan Syariah, 2022)
The purpose of this study is to determine the factors it hat cause a decrease in the financing of BPRS Al-washliyah ieen from Third Party Funds (DPK), Non Performing Financing (NPF), Return On Assets (ROA) and Capital Adequacy Ratio (CAR) affect financing. The population in this study is BPRS Al-washliyah. The dependent variable (Y) of this study is the financing of the Al-washliyah BPRS .The independent variables (X) include: Third Party Funds (DPK), Non Performing Financing (NPF),Capital Adequacy Ratio (CAR) and Return On Assets (ROA). The methodius ediisi quantitativeire search methodiusing SPSS20.0 data analysis. Basedion multiple regression analysis, the results showed that Third Party Funds (DPK) affected the financing of BPRS Alwahilyah, Non Performing Financing (NPF) did not affect the financing of BPRS Al-washliyah,Capital Adequacy Ratio (CAR) did not affect the financing of BPRS Al-washliyah, Returnion Assets (ROA) affect the financing of BPRS Alwahilyah.